2022
DOI: 10.1038/s41467-022-30397-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulating gene regulation function by chemically controlled transcription factor clustering

Abstract: Recent studies have suggested that transcriptional protein condensates (or clusters) may play key roles in gene regulation and cell fate determination. However, it remains largely unclear how the gene regulation function is quantitatively tuned by transcription factor (TF) clustering and whether TF clustering may confer emergent behaviors as in cell fate control systems. Here, to address this, we construct synthetic TFs whose clustering behavior can be chemically controlled. Through single-parameter tuning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Previous studies have suggested that TF concentration regulates transcriptional bursting kinetics 26 , 43 , 77 . Moreover, strong enhancers drive bursts at a higher frequency than weak enhancers, while SEs exhibit similar bursting patterns to strong enhancers, showing relatively longer burst duration and higher burst amplitude 23 , 78 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have suggested that TF concentration regulates transcriptional bursting kinetics 26 , 43 , 77 . Moreover, strong enhancers drive bursts at a higher frequency than weak enhancers, while SEs exhibit similar bursting patterns to strong enhancers, showing relatively longer burst duration and higher burst amplitude 23 , 78 .…”
Section: Discussionmentioning
confidence: 96%
“…Our work suggests that the awareness of RNA bifunctionality is not only of conceptual importance, but will be increasingly useful when nascent RNA acts as a general binding platform to recruit transcription regulators. Previous studies have suggested that TF concentration regulates transcriptional bursting kinetics 26,43,77 . Moreover, strong enhancers drive bursts at a higher frequency than weak enhancers, while SEs exhibit similar bursting patterns to strong enhancers, showing relatively longer burst duration and higher burst amplitude 23,78 .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, an important open question is how clustering influences TFs during the different steps of transcription activation 13,[21][22][23] . Clustering and IDR-mediated interactions have been reported to enhance target search (increasing the DNA binding rate) [24][25][26][27][28] , to increase the local concentration of TFs at the promoter (increasing the DNA binding rate), to stabilize TF binding to DNA (decreasing the rate of TF unbinding) 12 , to enable 3D genomic interactions between target genes 29 and to boost transcription activation through enhanced recruitment of cofactors and polymerase molecules 30,20,16,31,32 . In contrast, clustering of synthetic TFs and the oncogenic TF EWS::FLI1 instead inhibit gene expression 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…The control primers for human RPL30 were provided with the kit. The process of RT-qPCR was carried out according to described previously [26,27] .…”
Section: Methodsmentioning
confidence: 99%